Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41598-017-17744-w
|View full text |Cite
|
Sign up to set email alerts
|

AICAR suppresses TNF-α-induced complement factor B in RPE cells

Abstract: Age related macular degeneration is the leading cause of blindness in the developed world. Although its precise cause remains elusive, dysfunction of the retinal pigment epithelium (RPE) and dysregulation of complement have been implicated in its pathogenesis. The goal of this study was to evaluate the role of an AMP-dependent kinase (AMPK) activator, 5-aminoimidazole-4-carboxamide riboside (AICAR), on tumor necrosis factor alpha (TNF-α) induction of complement factor B (CFB) in RPE cells. We found that AICAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Acadesine, can exert its effects through either extracellular or intracellular mechanisms. To examine if acadesine’s effects are mediated via an extracellular or via an intracellular mechanism we used dipyridamole (DPY) which blocks the cell membrane adenosine transporters and prevents acadesine uptake into the cells [ 37 ]. Pretreatment with 4 μM of DPY abolished the effect of acadesine on TNF-α induced C3 protein expression in both human primary and ARPE-19 cell lysates ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Acadesine, can exert its effects through either extracellular or intracellular mechanisms. To examine if acadesine’s effects are mediated via an extracellular or via an intracellular mechanism we used dipyridamole (DPY) which blocks the cell membrane adenosine transporters and prevents acadesine uptake into the cells [ 37 ]. Pretreatment with 4 μM of DPY abolished the effect of acadesine on TNF-α induced C3 protein expression in both human primary and ARPE-19 cell lysates ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This result is in agreement with previous studies in which inflammatory cytokines like TNF-α induced complement component synthesis [ 48 , 49 ]. Acadesine has anti-inflammatory properties [ 33 , 34 , 37 , 45 ], is an exercise mimetic [ 71 , 72 ] and has been used in human clinical trials as a cardioprotectant [ 73 , 74 ]. Pre-treatment of human RPE cells with the AMP analog, acadesine, downregulated TNF-α induced C3 and its cleaved products C3α and C3β.Cleavage of C3 alpha chain leads to C3a, which is an anaphylatoxin and is implicated in a variety of studies with AMD pathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CFB protein is produced in several parts of the eye including the choroid, RPE, and neural retina 11 . Previous studies have shown that pro-inflammatory cytokines of TNF-α and IFN-γ can up-regulate the expression of CFB in RPE cells 12, 13. A study performed by Crowley et al.…”
Section: Introductionmentioning
confidence: 99%